EKSISTENSI KEBIJAKAN DAERAH YANG DEMOKRATIS DALAM SISTEM PEMERINTAHAN YANG BERSIH BEBAS DARI KORUPSI - Ismail, Ismail (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT.One of the challenges in realizing democratic local policies is the political culture that tends to be patrimonial and lacks emphasis on democratic values. Practices such as political money, patronage, and nepotism often hinder the democratization process at the local level. This research examines the impact of democratic local policies on efforts to establish a clean government system free from corruption, as well as the factors that hinder the implementation of democratic local policies in supporting good governance. Normative legal research is a process to find legal rules, legal principles, and legal doctrines to answer legal problems. Democratic regional policies have a significant impact in promoting the establishment of a clean government system free from corruption. By prioritizing the principles of transparency, accountability, and community participation, these policies can narrow the space for corrupt practices and create more effective oversight mechanisms. Furthermore, the implementation of democratic regional policies faces various obstacles, such as low human resource capacity in local government, weak oversight mechanisms, a political culture that is not supportive, and minimal community participation. Keywords: Regional Policy, Democratic, Corruption.